Mess : a novel - Chessler, Michael (Harper Paperbacks, 2025)
"Marie Kondo meets The Real Housewives in this charming and perceptive story of a professional organizer to Hollywood's elite who learns to find love and acceptance amid the messiness of life. To the world, Jane Brown, a Los-Angeles based professional organizer, is a model of composure and reticence. But inside, she's fiercely judgmental and critical of herself and others. A lover of order and tidiness, she struggles to accept the world's exasperating messiness of both her own clients-a superficial sphere of influencers and rich creatives-and her live-in boyfriend, who is becoming as aggravating as he is comforting. When she arrives at the home of a new client, a has-been Hollywood actress-a woman opposite to her in every way-Jane finds herself unexpectedly moved. Realizing how desperately she wants to lower her defenses and open her heart, Jane decides to declutter the mess of her own mindset. Organizing her own feelings turns out to be the most daunting job she's ever tackled, but one that promises big rewards if she succeeds, including freedom-and even love. Set against the dazzlingly rich, beautiful, and shallow world of Hollywood money and mansions, Mess is an honest, heartfelt, and often hilarious response to the disorder of our lives today"-- Provided by publisher.